1998
DOI: 10.1111/j.1600-0528.1998.tb02092.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and behavioral issues in early childhood caries

Abstract: Rampant caries in infants and young children has long been recognized as a clinical syndrome referred to by various names, including nursing caries, nursing bottle syndrome, night bottle mouth, and baby bottle tooth decay. The common theme among these terms is the perceived central role of inappropriate use of the baby bottle in the etiology and progression of carious lesions. Use of the baby bottle is not the only, and may not be the most important, factor in caries development. Because of questions about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
0
44

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 72 publications
5
137
0
44
Order By: Relevance
“…Os resultados desse estudo igualmente revelam a elevada ocorrência de problemas de saúde bucal nas crianças estudadas, a maioria preveníveis e controláveis, tais como a cárie dentária, as alterações gengivais e as maloclusões, os quais podem interferir negativamente no desenvolvimento físico e emocional dos pré-escolares acometidos. 28 Para controlá-los e minimizá-los são possam contribuir a melhoria da condição de saúde bucal nesse grupo.…”
Section: Resultsunclassified
“…Os resultados desse estudo igualmente revelam a elevada ocorrência de problemas de saúde bucal nas crianças estudadas, a maioria preveníveis e controláveis, tais como a cárie dentária, as alterações gengivais e as maloclusões, os quais podem interferir negativamente no desenvolvimento físico e emocional dos pré-escolares acometidos. 28 Para controlá-los e minimizá-los são possam contribuir a melhoria da condição de saúde bucal nesse grupo.…”
Section: Resultsunclassified
“…Considera-se que a classe social pode influenciar o risco à cárie de vá-rias formas: indivíduos de nível sócio-econô-mico inferior têm desvantagens sociais e materiais que influenciam a habitação, a habilidade para prover adequada nutrição e emprego estável 26 , além de comprometer sua habilidade em preocupar-se consigo mesmo, obter cuidado por parte de profissionais de saúde e viver em ambiente saudável 27 . Ressaltando, ainda, que todos esses fatores conduzem a uma resistência reduzida às doenças bucais entre outras enfermidades 28 .…”
Section: Discussionunclassified
“…Embora o uso inadequado da mamadeira seja o fator relacionado, com maior freqüência, à cárie precoce 38 , não existe consenso absoluto sobre essa ligação, uma vez que muitos estudos demonstraram que nem sempre o uso de mamadeira com leite ou outra substância causou cárie 26 .…”
Section: Discussionunclassified
“…Usually the pattern of sugar consumption increases during the first two years of children life and various research studies conducted on feeding habits and sugar intake among children established the fact that it promotes early childhood caries (ECC). However it has been reported in few research studies that actually it is the interplay of multiple factors which is found to be associated with ECC and it remains controversial finding [42][43][44]. The frequent intake of sugary snacks has also been associated with ECC [45,46].…”
Section: Role Of Mothers In Prevention Of Early Childhood Caries and mentioning
confidence: 99%